The Influence of Work Discipline, Work Motivation, Work Spirit, and Job Training on Employee Performance at PT. Nasha Poultry Indonesia - Lubis, Azira Asiawati; Pasaribu, Abdul Halim; Elvina, Elvina (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this research is to determine and analyze the influence of work discipline on employee performance, to determine and analyze the influence of motivation on employee performance, then to determine and analyze work morale on employee performance, as well as to determine and analyze work training on employee performance at PT. Nasha Poultry Indonesia - West Sumatra. This research uses associative research with a sample of 101 respondents who are employees of PT. Nasha Poultry Indonesia. The data collection technique uses a list of questions such as a questionnaire and the data analysis technique uses Partial Least Square (SmartPLS) to test the four hypotheses proposed in this research. The research results show that: 1. Work Discipline has no negative and insignificant effect on the performance of employees at PT. Nasha Poultry Indonesia, then 2. Work Motivation has a negative and insignificant effect on the performance of employees at PT. Nasha Poultry Indonesia, 3. Work morale has a positive and significant effect on the performance of employees at PT. Nasha Poultry Indonesia, and 4. Job Training has a positive and significant effect on employee performance at PT. Nasha Poultry Indonesia.